PENGARUH INFLASI DAN SUKU BUNGA BI TERHADAP RETURN OF ASSET (ROA) DI PT.BANK DANAMON INDONESIA TBK PERIODE 2015-2019 - Zahra, Firlia Adnina; Manda, Gusganda Suria (COMPETITIVE, 2023)
It is undeniable, almost all banks in Indonesia have an important role for the country's economy. The purpose of this study is to determine whether inflation and interest rates at Bank Indonesia have an influence on the Return Of Assets (ROA) at Bank Danamon for the 2015-2019 period. In the period from 2015 to 2019, interest rates at Bank Indonesia and inflation increased and decreased. The secondary data used in this study were taken through the IDX and the official website of Bank Danamon itself. Then, the quantitative research method becomes the method in this study, where the data to be processed is the annualnfinancial statements ofnBank Danamon for the 2015 to 2019 period. It can be concluded that a significant relationship is not seen in the inflation variable and BI interest rates on the Return Of Assets (ROA) variable.